Clinical Holistic Medicine: Holistic Pelvic Examination and Holistic Treatment of Infertility - Søren Ventegodt; Mohammed Morad; Joav Merrick (The Scientific World Journal)
In clinical holistic practice, it is recommended that ample time is spent with the gynecological or pelvic examination, especially in cases of women with suspected old emotional traumas following early childhood cases of incest or sexual abuse. The holistic principles of holding and processing should be followed with the purpose of healing the patient, re-establishing the natural relationship with the body, sexuality, and reproductive organs. Sexual violations are often forcibly repressed. It appears that the tissues that were touched during the violation often bear the trauma. It is characteristic of these patients that their love lives are often problematic and do not provide the necessary support to heal the old wounds in the soul and therapy is therefore indicated. When this is concerned with the reproductive organs, it poses particular difficulties, as the therapy can easily be experienced as a repetition of the original violation, not least due to the risk of projection and transference. There is, therefore, a need for a procedure that is familiar to and safe for the patient, for all work that involves therapeutic touching of sexual organs over and beyond what is standard medical practice. This paper presents one case story of earlier child sexual abuse and one case of temporary infertility. We have established a procedure of slow or extended pelvic examination, where time is spent to make the patient familiar with the examination and accept the whole procedure, before the treatment is initiated. The procedure is carried out with a nurse, and 3 h are set aside. It includes conversation on the present condition and symptoms; concept of boundaries; about how earlier assaults can be projected into the present; establishment of the therapeutic room as a safe place; exercises on when to say stop; therapeutic touch; visualization of the pelvic examination step by step beforehand; touching on the outside of the clothes with repetition of the stop procedure if necessary; pelvic examination paying special attention to traumatized (damaged/scarred/blocked) areas with feel, acknowledge, and let go of the traumatized areas; postprocessing of emotions and traumas with final healing. The patient cannot be healed until negative decisions are found and dropped with a tour back to the present, to let go of negative sentences and ideas, and a plan for further positive progress.